Realtime Analysis of Large-Scale Data - Becker, Daniel (KIT Scientific Publishing, 2017)
In photon science more and more data are taken. It is not possible anymore to store and process all data offline. In this book, we explore strategies for handling this large amount of data. A neural network as well as techniques from image processing are used to efficiently categorize and select useful data. We also indicate why many sophisticated algorithms cannot be used in this context. In addition, a prototype for data selection is presented, discussed, and benchmarked.